LITERATURE REVIEW: THE EFFECTIVENESS OF PROJECT-BASED LEARNING IN DEVELOPING SOCIAL AND COGNITIVE SKILLS OF SECONDARY SCHOOL STUDENTS - Firdausih Firdausih; Yusnelli Yusnelli; Al-Amin (Adisam Publisher, 2025)
The effectiveness of project-based learning (PjBL) in developing social and cognitive skills of secondary school students. PjBL can create a learning environment that supports active and collaborative interaction among students, which contributes significantly to the development of social skills such as co-operation, communication and adaptation in groups. In addition, PjBL is also proven to be effective in improving students' cognitive skills, including critical thinking, information analysis, and creative problem solving. Through active engagement in relevant and challenging projects, students are motivated to learn and develop effective learning strategies. Overall, PjBL is a comprehensive learning approach that not only prepares students for academic challenges, but also supports the development of essential skills needed in future life and careers.